2001
DOI: 10.1377/hlthaff.20.3.43
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Reports On Hospital Care In Five Countries

Abstract: The current nursing shortage, high hospital nurse job dissatisfaction, and reports of uneven quality of hospital care are not uniquely American phenomena. This paper presents reports from 43,000 nurses from more than 700 hospitals in the United States, Canada, England, Scotland, and Germany in 1998-1999. Nurses in countries with distinctly different health care systems report similar shortcomings in their work environments and the quality of hospital care. While the competence of and relation between nurses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
1,099
9
82

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,314 publications
(1,263 citation statements)
references
References 11 publications
48
1,099
9
82
Order By: Relevance
“…The findings that 'opportunities to practice the professional role of nursing' and 'unscheduled work' contributed significantly to the production of stress is consistent with the findings of a study done on 43.000 nurses in USA, Canada, England, Scotland, and Germany (Aiken et al, 2001). This study found that in all of these countries, except Germany, minority of nurses perceived that they have opportunities for advancements.…”
Section: Discussionsupporting
confidence: 87%
“…The findings that 'opportunities to practice the professional role of nursing' and 'unscheduled work' contributed significantly to the production of stress is consistent with the findings of a study done on 43.000 nurses in USA, Canada, England, Scotland, and Germany (Aiken et al, 2001). This study found that in all of these countries, except Germany, minority of nurses perceived that they have opportunities for advancements.…”
Section: Discussionsupporting
confidence: 87%
“…The environment of professional nursing practice has been the focus of national and international studies, due to two factors, the first related to the quality of care provided, with the main aspect being patient safety (1)(2) and the second, related to the reduction or the shortage of these professionals (3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in the length of hospital stays combined with increases in patient acuity, heavier nursing workloads, and sparse staffing are the unfortunate results of these cost saving measures [2][3][4] . Recent studies show that Hospital-based bedside nurses are burnedout, emotionally exhausted, and highly dissatisfied with their jobs 5 . Given the current and ongoing nursing shortage, the detrimental effects on the nursing workforce from unsupportive and under staffed work environments predicts poor prospects for recruiting adequate numbers of nurses and gives cause for concern when countries grapple with the serious current and projected shortfall in the supply of nurses.…”
Section: Introductionmentioning
confidence: 99%